Three-dimensional architecture and assembly mechanism of the egg-shaped shell in testate amoeba Paulinella micropora - Nomura, Mami; Ohta, Keisuke; Nishigami, Yukinori; Nakayama, Takuro; Nakamura, Kei-Ichiro; Tadakuma, Kenjiro; Galipon, Josephine (Frontiers in Cell and Developmental Biology, 2023)
Unicellular euglyphid testate amoeba Paulinella micropora with filose pseudopodia secrete approximately 50 siliceous scales into the extracellular template-free space to construct a shell isomorphic to that of its mother cell. This shell-constructing behavior is analogous to building a house with bricks s, and a complex mechanism is expected to be involved for a single-celled amoeba to achieve such a phenomenon; however, the three-dimensional structure of the shell and its assembly in P. micropora are still unknown. In this study, we aimed to clarify the positional relationship between the cytoplasmic and extracellular scales and the structure of the egg-shaped shell in P. micropora during shell construction using focused ion beam scanning electron microscopy (FIB-SEM). Three-dimensional (3D) reconstruction revealed an extensive invasion of the electrondense cytoplasm between the long sides of the positioned and stacked scales, which was predicted to be mediated by actin filament extension. To investigate the architecture of the shell of P. micropora, each scale was individually segmented, and the position of its centroid was plotted. The scales were arranged in a left-handed, single-circular ellipse in a twisted arrangement. In addition, we 3D printed individual scales and assembled them, revealing new features of the shell assembly mechanism of P. micropora. Our results indicate that the shell of P. micropora forms an egg shape by the regular stacking of precisely designed scales, and that the cytoskeleton is involved in the construction process.